THE REGULATION AD HOC NORMATIVE IN MULTIFAMILY BUILDINGS IN THE MAGDALENA DEL MAR DISTRICT, LIMA, PERU: CASE STUDIES - Carrión-Ansuini, Víctor Antonio (2020)
This research describes the ad hoc normative regulation in multifamily buildings applied in the Magdalena del Mar district, Lima, Peru, which allowed us to have a current look at how the urban planning legislation for the interior of the district was being structured, which in recent years the municipal administration and previous periods, decided to carry out management with a vision from generating a real estate, economic and pro-investor dynamics, the result of which was evidenced in the increase in the value of the lot per m2, mainly linked to the "maximum height ”and consequently to the generation of“ real estate capital gains ”. It was important to address the subject since there were no similar investigations in Peru, and, therefore, it clarifi ed various paradigms regarding the principles of order and disorder, growth, development and urban transformation over time, presented in the population, in professionals of diverse specialties in the matter, journalists, authorities, civil servants and others; that by relating them to "urban law" as a source for the construction of the theoretical framework, a specialty not fully developed, contributed positive results to the deduction of the proposed management. Keywords: Urban law - urban planning legislation - real estate surplus value - normative regulation